2017
DOI: 10.1089/jpm.2017.0039
|View full text |Cite
|
Sign up to set email alerts
|

The Palliative Care Challenge: Analysis of Barriers and Opportunities to Integrate Palliative Care in Europe in the View of National Associations

Abstract: A set of barriers and opportunities to PC integration has been identified across Europe, by national associations, offering a barometer against which to check the challenge of integration across countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 23 publications
2
51
0
5
Order By: Relevance
“…Globally, there are increasing calls for reforms that would allow government health agencies to integrate palliative care into primary care [51,55,56]. However, it is still unclear how such integration would be achieved and the process is likely to be challenging [57][58][59]. Lack of both standardised clinical pathways and systems for informationsharing have impeded the establishment of stable and integrated EOL care across relevant agencies [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, there are increasing calls for reforms that would allow government health agencies to integrate palliative care into primary care [51,55,56]. However, it is still unclear how such integration would be achieved and the process is likely to be challenging [57][58][59]. Lack of both standardised clinical pathways and systems for informationsharing have impeded the establishment of stable and integrated EOL care across relevant agencies [60].…”
Section: Discussionmentioning
confidence: 99%
“…Internal players (i.e. primary care and palliative care providers, local healthcare organisations) should ensure local needs and capacity are fully considered, whereas external players need to strengthen healthcare infrastructures through evidencebased decisions on funding, staffing, regulation and legislation [58,60,64].…”
Section: Discussionmentioning
confidence: 99%
“…Although the consistency of our results with other studies supports the validity of the findings, further research with an additional sample of IPC leaders may be helpful to confirm our findings. As a result, another InSup-C study by Centeno et al (2017) investigated leaders’ opinions on barriers and opportunities to the integration of palliative care according to levels of service provision across Europe. Notwithstanding these limitations, this study is a good starting point for further in-depth investigation of IPC.…”
Section: Discussionmentioning
confidence: 99%
“…Less is known about factors associated with long-term sustainable implementation, which may be different from those affecting short-term implementation. In addition, studies have shown difficulties when implementing palliative care in general healthcare settings where there is not an exclusive focus on patients in the palliative phase, such as home-care and hospital settings [7][8][9][10][11]. This study provides insight into strategies and factors affecting sustainable implementation of innovations in palliative care in a nationwide Dutch Quality Improvement Programme in which palliative care innovations were implemented mainly in general healthcare settings.…”
Section: Introductionmentioning
confidence: 95%